Anti-Atherogenic And Antioxidant Activities Of Patawali (Tinospora Crispa) On Rabbits Fed With High Cholesterol Diet - Bahari, Hasnah (2008)

(untitled)
Tinospora crispa is a wild plant in Malaysia. Malay community used this plant traditionally for various therapeutic purposes. Despite many studies conducted on its antidiabetic and antipyretic effects, no study has been designed to address the question whether T.crispa could work as an antioxidant and lipid lowering agent. The aim of this experiment is to study the lipid lowering and antioxidant effects of T.crispa in rabbits fed with high cholesterol diet. The in vitro study was conducted to determine the total antioxidant activity of T.crispa aqueous extract. The scavenging activity of T.crispa measured using DPPH analysis was 85.95±0.52%. The antioxidant activity of T.crispa measured via TBA test and FRAP assay was 39.20±2.97% and 0.89+0.03mmol/L respectively. The types of flavonoids found in T.crispa were catechin, luteolin, morin and rutin. Thirty male New Zealand White rabbits were randomly divided into six groups for the in vivo studies. The normal control (NC) group was fed 100g/rabbit/day normal rabbit chow. Positive control (PC) and Simvastatin control (SC) groups were fed high cholesterol diet (HCD) (0.5% cholesterol). The SC group was supplemented 5 mg/kg/day of Simvastatin. The treatment groups (T150, T300 and T450) were fed with HCD and 150, 300 and 450 mg/kg/day of T.crispa extract respectively. The experimental period was designed for 10 weeks. Ear vein blood sampling were collected at week 0 (w0), week 5 (w5) and week 10 (w10) for plasma analysis. At the end of the experiment, the animals were sacrificed via exsanguinations, the aorta were excised and examined for histomorphometric analysis. Through plasma analysis, the activity of gamma glutamyl transferase (GGT), aspartate amino transferase (AST) and alanine amino transferase (ALT) were significantly lower (p<0.05) in group T450 at w10 compared to group PC. Group T150 and T300 had a significantly lower (p<0.05) total cholesterol (TC) level compared to PC at w10. Group T450 had a significantly higher (p<0.05) TC level against PC. All groups supplemented with T.crispa had a significantly higher (p<0.05) in high density lipoprotein (HDL) level and significantly lower (p<0.05) LDL level compared to PC at w10. The TG level of T150 and T450 were significantly decreased (p<0.05) from w5 to w10. Activity of catalase (CAT) in T150, T300 and T450 were significantly lower (p<0.05) at w10 compared to PC. Group T450 had significantly higher (p<0.05) total antioxidant activity (TAA), glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) activities compared to PC at w10. No foam cell formation was visible in aorta of rabbits in group NC, SC and T450. However, there were visible foam cell formation in the aorta of group PC, T150 and T300. In conclusion, this study suggested that supplementation of 450 mg/kg of T.crispa extract would be able to reduce or retard the progression of atherosclerotic plaque development induced by dietary cholesterol. The enhanced serum HDL, increase in antioxidant status and flavonoids composition may be the possible underlying mechanisms of antiatherogenic effect of T.crispa.